2017
DOI: 10.1016/j.ijppaw.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Co-introduction of ancyrocephalid monogeneans on their invasive host, the largemouth bass, Micropterus salmoides (Lacepéde, 1802) in South Africa

Abstract: Largemouth bass, Micropterus salmoides (Lacepéde, 1802) were sampled from three provinces (Eastern Cape EC, North West NWP and KwaZulu-Natal KZN) in South Africa to assess for parasite diversity and community composition. Morphological evaluation of the sampled parasite specimens provided evidence for the first record of five monogeneans from the family Ancyrocephalidae: Clavunculus bursatus (Mueller, 1963), Onchocleidus dispar (Mueller, 1936), Onchocleidus furcatus (Mueller, 1937), Onchocleidus principalis (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…For example, five ancyrocephalid monogeneans are found only on the alien Largemouth Bass, Micropterus salmoides. Despite the almost ubiquitous presence of bass in South African rivers (Ellender et al 2014), these parasites have not been observed to infect native fishes to date (Truter et al 2017). The other seven co-introduced parasites, however, have formed new associations with native hosts, probably because of broader levels of generalism in their symbiotic requirements (Smit et al 2017).…”
Section: Freshwater Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, five ancyrocephalid monogeneans are found only on the alien Largemouth Bass, Micropterus salmoides. Despite the almost ubiquitous presence of bass in South African rivers (Ellender et al 2014), these parasites have not been observed to infect native fishes to date (Truter et al 2017). The other seven co-introduced parasites, however, have formed new associations with native hosts, probably because of broader levels of generalism in their symbiotic requirements (Smit et al 2017).…”
Section: Freshwater Fishmentioning
confidence: 99%
“…Some alien fishes in South Africa have considerably lower parasite loads than in their native ranges. In an assessment of the parasitism of largemouth bass for example, Truter et al (2017) documented lower parasite abundance and richness in South Africa in comparison with native range populations. This may explain why this species managed to invade a wide range of habitats throughout southern Africa despite extremely low genetic diversity, resulting from a very limited number of propagules introduced into South Africa in the late 1920s (Hargrove et al 2017).…”
Section: Freshwater Fishmentioning
confidence: 99%
“…For example, no spillover to native fishes has been reported for the six ancyrocephalid monogeneans found on Black Bass (Micropterus spp. ), despite the almost ubiquitous presence of its fish hosts in South African ecosystems (Truter et al 2017). Others, such as the Asian Tapeworm Schyzocotyle acheilognathi, are not only widespread, but have also spilled over to several native taxa (Smit et al 2017).…”
Section: Platyhelminthesmentioning
confidence: 99%
“…(2017) provide an up-to-date list of non-native parasites recorded on South African freshwater fishes, one of the very rare such regional compilations. Then, Truter et al. (2017) report that largemouth bass, Micropterus salmoides , introduced to South Africa from North America, has left behind its endohelminths but co-introduced several monogenean species, adding to the list of invasive parasites in South African freshwaters.…”
Section: This Special Issue On ‘Invasions’mentioning
confidence: 99%